Islamic by-laws executed by local government at Kelantan: Learning referral / Suzei Mat Nurudin ... [et al.] - Mat Nurudin, Suzei; Mohd Zain, Zarin; Yaacob, Nurain; Safiin, Rasukhan (2023)
Islamic By-Laws executed by local government at Kelantan: Learning Referral is about the innovation products that has been created from the internal grants dispensed by the Faculty of Administrative Science and Policy Studies (FSPPP) Universiti Teknologi MARA (UiTM) 2021. From the grant, several publications have been made and joining innovation competitions such as International Invention & Innovative Competition (InIIC) 2022 and International Creative Innovation Idea Competition (ICIIC) 2023. The innovation started with the project called By-Laws Potrayal: Local Authority Exertion. The innovation is in the form of an infographic poster created with the compilation of an insightful local government by law information that have Islamic approach consisting of related pictures, findings of local authorities views and others information related that purposely related for providing the needed information for the local communities at Kelantan. The second innovation is in a form of a book named By-Laws Influence in Shaping the Society's Behavior - A Monograph which is a simple but extensive book created with the compilation of an insightful local government Islamic by-laws implementation.